Парадигма современной географии: от ретроспекции к соционоосферному направлению - Багров, Н.В. (Український географічний журнал, 2011)
У сучасному глобалізованому світі дуже гостро постає питання про те, які шляхи можуть привести нас у якісно інше майбутнє, якою має бути відповідь науки на виклики часу. У статті розглядається, якою має бути географія. Особливо наголошується на необхідності кардинального оновлення нашої науки за умов, коли зовсім іншим стає поняття географічного простору, докорінно змінюється зміст об’єкта й предмета науки. Сьогодні потрібна географія як метод формування диференційованої картини світу стосовно кожної структури суспільства. На думку автора, це має бути соціоноосферна географія. Викладено зміст і завдання цієї нової галузі географії, що починає зароджуватися. In the modern globalized world it has considerable importance the question about the ways that can lead us into qualitatively different future, the question of what has to be the science’s answer to the modern challenges. In the paper it is considered what geography has to be. It is especially emphasized on the necessity of cardinal renewal of geography under conditions when understanding of geographic space is becoming basically different, the contents of object and subject of the science is radically changing. Today there is a need of geography as the methodology for creation of differentiated picture of the world regarding each structure of society. In the author’s judgment, it has to be socionoospheric geography. It is described the contents and tasks of this new branch of geography, that is beginning to develop.